النتائج الوظيفية للعلاج المحافظ لكسور النهاية السفلية للكعبرة عند البالغين - سعد, معن; المحمد, عزة; محمد, حسام (Latakia University Journal -Medical Sciences Series, 2018)
This study was carried out in AL-ASSAD University Hospital in Lattakia during one year 2015-2016 and included 60 patients, Male :Female ratio was 42%:58%, the peak incidence was in and decades 48%, the most common cause was simple falling 72.37%, the most dominant hand was the right hand 90% of patients, and the most cases included the right hand 70%, most cases was closed fractures 93.3%, the most common type of fracture was type A2 in 45% of cases, the clinical results was divided into 4 groups according to qDASH score: (73.33% good , 15%excellent , 8.33%intermediate , 3.33%bad). أجريت الدراسة في مشفى الأسد الجامعي في مدينة اللاذقية ، وتضمنت الدراسة عدداً من كسور النهاية السفلية للكعبرة خلال فترة سنة كاملة 2015-2016 ، وشملت الدراسة 60 مريضاً . وكانت نسبة إصابة الذكور إلى الإناث 42% الى 58% مع ذروة حدوث في العقدين الرابع والخامس بنسبة 48%، وكان السبب الأشيع لمعظم الاصابات هو السقوط البسيط بنسبة 72.37% , وكانت اليد اليمنى هي اليد المسيطرة عند 90% من المرضى، أغلب الاصابات شملت اليد اليمنى 70% من الحالات، ومعظم الكسور كانت من النوع المغلق 93.3%، معظم الكسور كانت من النمط ِA2 بنسبة 45%، وتوزعت النتائج السريرية وفق نظام qDASH الى أربع مجموعات :(73.33% جيدة،15% ممتازة، 8.33% متوسطة، 3.33% سيئة).